Financial Globalisation and Economic Transformation in Africa: Evidence from Nigeria - Patrick Idode; Gbenga Sanusi (Nauki o Finansach)
This study examines the effects of financial globalisation on the Nigerian economy using data from the Central Bank of Nigeria statistical bulletin and the Nigeria Bureau of Statistics reports from 1992 to 2017. Using both descriptive and inferential statistical analyses, the study reveals that financial globalisation has helped to mobilise foreign direct investment into the economy and the significant positive effect of personal remittances on per capita income of Nigerians. Therefore it recommends that favourable policies to attract and retain FDI and personal remittances from developed nations should be encouraged and African governments and economic actors should consider all stakeholders' interests, and ensure that an international financial and trade system is "fair and reciprocal" to eliminate the persisting trends in abject poverty, predatory trade policies and the escalation of economic inequalities in Africa.(original abstract)